Implementasi Program Bintang Kelas Untuk Menunjang Partisipasi Aktif Peserta Didik Saat Pembelajaran Dikelas - Hidayat, Moh. Syamsul; Abidin, Zaenal (CV. Kurnia Grup, 2025)
A common problem that is often encountered is that students are not active enough in classroom learning. The large number of passive students can lower student achievement and even prevent the achievement of predetermined learning outcomes. This study will focus on the implementation of the class star program. This program aims to support active student participation during the learning process. The research method involves students as subjects and teachers as implementers of the program. The program will last for 4 weeks and involve 25 students. A questionnaire will be given to teachers who implement the class program in their classrooms. The star results show that student participation increased, with an average of 6.16 stars per student. Participation was categorized as low (<5 stars) for 10 students (40%), moderate (5-9 stars) for 11 students (44%), and high (≥10 stars) for 4 students (16%). This shows a positive trend in student participation in the classroom. The results of the questionnaire show that teachers agree that the star student program can increase students' courage in expressing their opinions, their enthusiasm in answering questions from teachers after the material has been presented, and encourage a competitive classroom atmosphere through students' desire to get high grades. Teachers feel that this program is easy to implement in learning activities.